Interactions between octenyl-succinic-anhydride-modified starches and calcium in oil-in-water emulsions. (April 2018) - Lin, Quanquan; Liang, Rong; Zhong, Fang; Ye, Aiqian; Singh, Harjinder
Abstract: This study examined the effects of the interactions between octenyl succinic anhydride (OSA)-modified starches and calcium on the structure and stability of emulsions at neutral pH and pH 3.0. OSA-modified starches were characterized by Fourier transform infrared spectroscopy, and the interactions between starch and calcium in aqueous solutions and in emulsions were determined using turbidity, light scattering and confocal scanning laser microscopy. At pH 7.0, the OSA-modified starch solutions containing CaCl2 had greater turbidity and lower negative charge. The OSA-modified starch solutions at pH 3.0 had greater turbidity and lower zeta-potential than those at pH 7.0, but were not affected by the addition of CaCl2 . At pH 7.0, the particle size of OSA-modified starch emulsions increased and the size distribution changed from monomodal to bimodal when the concentration of added CaCl2 increased because of both flocculation and coalescence between emulsion droplets. Increasing the degree of substitution (DS) of the OSA-modified starch led to greater stability to coalescence but lower creaming stability of emulsions. At pH 3.0, the emulsions had larger particle size, remained stable and were not affected by the addition of CaCl2 . The observation of the coalescence occurred in the Ca 2+ -induced flocculated emulsions stabilized by low DS OSA-modified starches provided interesting information for emulsification and stability of starch-stabilized emulsions and application of modified starches. Graphical abstract: Image 1 Highlights: Calcium ions interact with OSA-modified starch in both aqueous solutions and emulsions. CaCl2 addition increased the droplet size of OSA-modified-starch-stabilized emulsions. Greater DS led to more flocculation and lower emulsion stability to creaming. Greater DS led to higher emulsion stability to coalescence.